From nerve net to nerve ring, nerve cord and brain: evolution of the nervous system - Arendt, Detlev; Tosches, Maria Antonietta; Marlow, Heather (Nature reviews. Neuroscience, 2016)
The puzzle of how complex nervous systems emerged remains unsolved. Comparative studies of neurodevelopment in cnidarians and bilaterians suggest that this process began with distinct integration centres that evolved on opposite ends of an initial nerve net. The 'apical nervous system' controlled general body physiology, and the 'blastoporal nervous system' coordinated feeding movements and locomotion. We propose that expansion, integration and fusion of these centres gave rise to the bilaterian nerve cord and brain.